Benzodiazepines: Uses, Dangers, and Clinical Considerations - Amber N. Edinoff; Catherine A. Nix; Janice Hollier; Caroline E. Sagrera; Blake M. Delacroix; Tunde Abubakar; Elyse M. Cornett; Adam M. Kaye; Alan D. Kaye (MDPI AG, 2021)
Benzodiazepines (BZDs) are among one of the most widely prescribed drug classes in the United States. BZDs are a class of psychoactive drugs known for their depressant effect on the central nervous system (CNS). They quickly diffuse through the blood-brain barrier to affect the inhibitory neurotransmitter GABA and exert sedative effects. Related to their rapid onset and immediate symptom relief, BZDs are used for those struggling with sleep, anxiety, spasticity due to CNS pathology, muscle relaxation, and epilepsy. One of the debilitating side effects of BZDs is their addictive potential. The dependence on BZDs generally leads to withdrawal symptoms, requiring careful tapering of the medication when prescribed. Regular use of BZDs has been shown to cause severe, harmful psychological and physical dependence, leading to withdrawal symptoms similar to that of alcohol withdrawal. Some of these withdrawal symptoms can be life threatening. The current treatment for withdrawal is through tapering with clonazepam. Many drugs have been tested as a treatment for withdrawal, with few proving efficacious in randomized control trials. Future research is warranted for further exploration into alternative methods of treating BZD withdrawal. This call to action proves especially relevant, as those seeking treatment for BZD dependence and withdrawal are on the rise in the United States.